Rice hull immobilized indigenous bacteria as a novel biofungicide against rice blast disease - Delgado, Aileen L.; Ballesteros, Florencio C., Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Plant root rhizospheric microbe natural interactions are essential for plant health, plant growth and disease suppression. Exploring the abilities of naturally occurring rice soil bacteria to reduce rice blast disease, caused by the fungal pathogen Magnaportheoryzae, could provide a sustainable solution to minimize the yield loss due to rice blast disease. In the Philippines alone yield losses ranging from 50-85% reported. Three isolates of rhizobacteria isolated from the rice field soil in University of the Philippines Los Banos were tested for their effectiveness to reduce rice blast disease intensity on rice cultivar UPLRI-5 under greenhouse conditions. The biofungicide was formulated with both rice hull mixture and liquid media which contained bacterial suspension of Bacillus subtilis 5, Bacillus cereus 3S5 and Pseudomonas fluorecens 10S2. Results of this study showed that all three formulas of rhizobacteria effectively reduced the rice blast intensity on cultivar UPLRi-5. The formula containing bacterial cells of P. fluorecens 10S2 showed the lowest rice blast disease intensity at 14.88% and the highest disease control at 85.12%. The control percentage resulted from this treatment was 33% higher compared to the control.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Rice blast disease -- Philippines; Rice hulls -- Philippines